Evaluation on the adaptability of shield cutter head system design. (March 2019) - Sun, Jianping; Li, Xiaopeng; Tang, Zhaoping
Abstract: The difference between the design adaptabilities of shield cutter head system has a strong impact on the tunnelling efficiency. How to study and evaluate its design adaptability is an urgent problem to be solved. In this paper, based on the membership matching degree of adaptability quality of shield cutter head system between the existing design and ideal design, and taking the matching degree as the initial data of the evaluation model, a design adaptability analysis model and evaluation method based on entropy weight improved TOPSIS are proposed. Taking the existing design of shield cutter head system as an example, the adaptability in subway construction are analysed and evaluated. The 9 adaptability indexes are ranked, and the conclusion is drawn that the adaptability of 17 design tasks of the cutter head system are general, which verifies the practicability and credibility of the method.